The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12906-020-02920-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ethyl acetate fraction from Semen sojae germinatum, the processed sprout of Chinese black soybean, on rat experimental osteoarthritis

Abstract: Background: Our previous in vitro study reported that the ethyl acetate fraction (EAF) of Semen sojae germinatum (SSG), the processed sprout of Chinese black soybean, possessed the potent anti-inflammatory and chondroprotective properties. The aim of the present work was to verify the in vivo antiosteoarthritic effect of EAF from SSG on a rat osteoarthritis (OA) model. Methods: A classical rat OA model was surgically induced by anterior cruciate ligament transaction (ACLT). The OA rats were intra-articularly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…As a key lymphokine, IL-6 mediates chemotaxis of inflammatory cells, exacerbates the inflammatory cascade, finally leads to tissue damage (Xie et al, 2021). In line with the known antiinflammatory properties of EAE of SSG (Wang et al, 2020;Fan et al, 2016) and other soybean bioactive compounds (Kusumah & Gonzalez de Mejia, 2022), the present study showed that, among different fractions extracted from SSG, the EAE appeared to exhibit the strongest inhibitory activity against the CCl 4 -induced liver inflammation.…”
Section: Effect Of Extracts From Ssg On the Levels Of Proinflammatory...supporting
confidence: 77%
See 3 more Smart Citations
“…As a key lymphokine, IL-6 mediates chemotaxis of inflammatory cells, exacerbates the inflammatory cascade, finally leads to tissue damage (Xie et al, 2021). In line with the known antiinflammatory properties of EAE of SSG (Wang et al, 2020;Fan et al, 2016) and other soybean bioactive compounds (Kusumah & Gonzalez de Mejia, 2022), the present study showed that, among different fractions extracted from SSG, the EAE appeared to exhibit the strongest inhibitory activity against the CCl 4 -induced liver inflammation.…”
Section: Effect Of Extracts From Ssg On the Levels Of Proinflammatory...supporting
confidence: 77%
“…In the modern experimental research, the CCl 4 -induced liver injury model has been well-accepted to share similar pathomechanisms, such as inflammatory damage, oxidative stress, and hepatocyte apoptosis, with chemical liver injury in humans (Li et al, 2018;Ahmad et al, 2023). Our previous studies showed that the extracts from SSG exerted the anti-inflammatory and anti-apoptotic activities in the in vitro and in vivo osteoarthritis models (Wang et al, 2020;Fan et al, 2016). Therefore, from the perspective of either TCM or modern scientific theory, it could be speculate that SSG and its active ingredients might have a protective effect on the CCl 4 -induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations